Implementación de Business Intelligence para la gestión de datos generados en el módulo de pedidos durante los años 2018-2021 en la empresa Marketing Digital Bravo & Beltrán - Quito Carrión, Luis Miguel (2023)
Currently, small and medium-sized enterprises face significant challenges regarding the management and analysis of large volumes of data. These companies often lack the necessary resources and expertise to turn this data into valuable and useful information for decision-making. BI is presented as a tool that allows these organizations to tackle these challenges. By using BI, companies can identify patterns and trends that enable them to make more informed and strategic decisions. In addition, the implementation of this tool provides greater visibility and transparency in business processes, improving customer confidence and increasing the profitability of the organization. Not using BI can have significant disadvantages for companies. The lack of strategic information can lead to inadequate decision-making and loss of business opportunities. Companies can find themselves dealing with a large amount of unstructured data, which makes it difficult to identify patterns and trends, delaying decision-making. In this context, the present TT implemented a Business Intelligence solution for the orders area of the Marketing Digital Bravo & Beltrán company, which properly manages the data generated in the company and converts it into valuable information that can be accessed more efficiently and timely through a dashboard, in order to support the decision-making process of the organization's manager. To achieve this objective, the work was developed in three phases. In the first phase, the organization's data was analyzed in order to establish the requirements and design of the data model, obtained through the use of the IEEE 830 standard. In the second stage, the necessary dimensions, measures, and fact tables were defined for the construction of the Data Warehouse, in addition to the implementation of ETL processes for its population. Finally, in the third stage, the implementation and deployment of the BI solution was carried out through a Dashboard. It is important to mention that for each stage of the TT, the phases of the methodology proposed by Ralph Kimball were used, and the Pentaho suite was used as a tool for the development of the BI solution. The results obtained in the TT consist of a dashboard that presents information on the organization's orders, companies, products, and users for the last three years. Through intuitive visual elements, this dashboard makes the information easier to understand and access, which benefits the company in reducing access time to information, improving decision-making, and overall performance. Keywords: Business Intelligence, Ralph Kimball, ETL processes.